Carbohydrate - Caliskan, Mahmut; Halil Kavakli, I.; Cevahir Oz, Gul (IntechOpen, 2017)
Carbohydrates are the most abound macromolecules on earth, and they serve different functions within the cell. The purpose of the book is to provide a glimpse into various aspects of carbohydrates by presenting the research of some of the scientists who are engaged in the development of new tools and ideas used to reveal carbohydrate metabolism in health and diseases and as material to mimic the carbohydrate surfaces that take part in molecular recognition, often from very different perspectives. This book covers broad topics in carbohydrate including quality carbohydrates on the prevention and therapy of noncommunicable diseases, lactate, and glycolysis, as biomass in biofuel production, targets for cancer treatment and as biomaterial.